Improving the Policy Framework in Japan to Address Climate Change - Jones, Randall S.. (OECD Economics Department Working Papers, 2009)
Japan, a relatively energy-efficient country, has been active in combating climate change. Under the Kyoto Protocol, Japan is committed to reducing greenhouse gas emissions by 6% relative to 1990 over the period 2008-12. As of 2007, however, its emissions were up by 9%. Japan has relied primarily on voluntary measures, which are monitored by the government, without binding commitments or price signals on carbon. It is essential to improve the policy framework to achieve its ambitious longer-term target of a 60% to 80% emission reduction by 2050 in a cost-effective manner. Japan should shift from voluntary measures to market-based instruments, notably a mandatory and comprehensive emission trading scheme, supplemented if necessary, by carbon taxes in areas not covered by trading, which minimise abatement costs and promote innovation to reduce emissions. Trading schemes should be linked to those in other countries, while expanding Japan's use of a well-functioning Clean Development Mechanism. Continued public support for R&D in emission reduction technology, particularly in basic research, is important